Intestinal colonization of infant hamsters with Clostridium difficile. - Rolfe, R D (1983)
Infant hamsters of different ages were examined for their susceptibility to enteric Clostridium difficile colonization. Intragastric administration of C. difficile to infant hamsters resulted in multiplication of the organism in the intestinal tracts of animals 4 to 12 days old; hamsters younger or older were resistant to C. difficile intestinal colonization. Toxicity to the colonized animals could not be demonstrated despite cytotoxin titers in some infant hamsters comparable to titers found in the intestinal tracts of adult hamsters with C. difficile-associated intestinal disease. When introduced into 4-day-old hamsters, C. difficile colonized the intestinal tract and remained at high levels until the animals were 13 days old, at which time the presence of intestinal C. difficile could no longer be demonstrated. The number of C. difficile required to colonize the intestinal tracts of 50% of 7-day-old hamsters was 18 viable cells. On the other hand, 10(8) viable cells of C. difficile failed to colonize the intestinal tracts of healthy, non-antibiotic-treated adult hamsters.